2022
DOI: 10.1177/10820132221074783
|View full text |Cite
|
Sign up to set email alerts
|

Surface conditioning with bacteriophages reduces biofilm formation of Salmonella Heidelberg

Abstract: Salmonella remains one of the most common foodborne pathogens worldwide, and its resistance to antimicrobials has increased considerably over the years. In this context, was evaluated the action of three bacteriophages isolated or combined in inhibiting the adhesion and removal of Salmonella Heidelberg biofilm on a polystyrene surface. The bacteriophages UPF_BP1, UPF_BP2, UPF_BP3 and a pool of them were used for biocontrol of Salmonella Heidelberg biofilms on polystyrene surface in the action times of 3, 6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Our study showed better results for the inhibition of Salmonella adhesion than for the removal of the preformed Salmonella biofilm. Similar results were found by Webber et al (2022) that demonstrated the effect of bacteriophages against S. Heidelberg biofilms. For studying preformed biofilms, the biofilms were allowed to form for 48 h, and were considered mature structures that hinder the action of the phage cocktail (Pires et al, 2017).…”
Section: Resultssupporting
confidence: 87%
“…Our study showed better results for the inhibition of Salmonella adhesion than for the removal of the preformed Salmonella biofilm. Similar results were found by Webber et al (2022) that demonstrated the effect of bacteriophages against S. Heidelberg biofilms. For studying preformed biofilms, the biofilms were allowed to form for 48 h, and were considered mature structures that hinder the action of the phage cocktail (Pires et al, 2017).…”
Section: Resultssupporting
confidence: 87%
“…Refer to Webber et al's methodology with minor modifications (48). Salmonella solution (100 μL, OD600 = 0.2) was added to 96-well plates and incubated at 37 °C for 72 h to form mature biofilms.…”
Section: Evaluation Of the Inhibitory Effect And Removal Of Salmonell...mentioning
confidence: 99%
“…Phages are the most abundant organisms in the biosphere, and they have been used in the health fields since the 1920s when they were first discovered by the French-Canadian microbiologist Félix d'Hérelle [ 68 , 69 ]. The application of bacteriophage has been considered a promising approach for controlling the biofilm formation of foodborne pathogens on the food industry surfaces [ 70 , 71 ]. Because phages can only infect bacteria, they are generally recognized as low toxic to human and eukaryote cells [ 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%